2016
DOI: 10.1051/0004-6361/201527801
|View full text |Cite
|
Sign up to set email alerts
|

Solar energetic particle access to distant longitudes through turbulent field-line meandering

Abstract: Context. Current solar energetic particle (SEP) propagation models describe the effects of interplanetary plasma turbulence on SEPs as diffusion, using a Fokker-Planck (FP) equation. However, FP models cannot explain the observed fast access of SEPs across the average magnetic field to regions that are widely separated in longitude within the heliosphere without using unrealistically strong cross-field diffusion. Aims. We study whether the recently suggested early non-diffusive phase of SEP propagation can exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 65 publications
(139 reference statements)
1
91
0
2
Order By: Relevance
“…The mean free paths presented in Figure 1 are consistent with those obtained using interplanetary turbulence properties (e.g. Pei et al 2010;Laitinen et al 2016;Strauss, Dresing & Engelbrecht 2017) and SEP observation analysis (e.g. Palmer 1982;Torsti, Riihonen & Kocharov 2004).…”
Section: Modelsupporting
confidence: 82%
See 2 more Smart Citations
“…The mean free paths presented in Figure 1 are consistent with those obtained using interplanetary turbulence properties (e.g. Pei et al 2010;Laitinen et al 2016;Strauss, Dresing & Engelbrecht 2017) and SEP observation analysis (e.g. Palmer 1982;Torsti, Riihonen & Kocharov 2004).…”
Section: Modelsupporting
confidence: 82%
“…While such a model is easy to implement and can be used as the first approach, as in, e.g., Laitinen et al (2016), we will consider here an improvement to the modelling of the transition, based on the work by Laitinen & Dalla (2017). In Appendix A, we derive a model with timedependent diffusion coefficient, which will justify fitting the variance with functional forms such as Equation (A6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Klein et al, 2008), or very high levels of lateral diffusion in a turbulent solar wind (e.g. Laitinen et al, 2016). The large spatial extent of global waves and their ability to accelerate particles far from the erupting active region therefore suggests that more SEP events should have been identified.…”
Section: Relationship With Solar Energetic Particle Eventsmentioning
confidence: 99%
“…Using the novel modelling approach introduced in L2013, Laitinen et al (2016) developed a particle transport model in the heliospheric Parker Spiral magnetic field configuration. They demonstrated that in moderate turbulence conditions, parametrised by the parallel scattering mean free path l k = 0.3 AU, fast spreading of SEPs across the field to a wide range of longitudes, as found by multi-spacecraft observations of SEP events (e.g.…”
Section: Introductionmentioning
confidence: 99%